PENGARUH KEKAYAAN DAERAH DAN KOMPLEKSITAS PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN WAJIB LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Jody Indra Ahmadi, - (2019)
This study aims to determine the effect of Regional Wealth and the Complexity of Local Governments on the Level of Mandatory Disclosure of Local Government Financial Reports. This study uses provinces throughout Indonesia as samples. The sampling technique uses a purposive sampling method. The sample in this study amounted to 101 provinces throughout Indonesia in 2015 to 2017. The data used was secondary data. Secondary data in this study originated from the Audit Report on the Regional Government Financial Reports published by the Supreme Audit Agency (BPK). Testing the hypothesis in this study uses Multiple Linear Regression nalysis with the SPSS 23 program and a significance level of 5%. The results of the study partially show that Regional alth has no significant effect on the Level of Disclosure of Local Government Financial Report Obligations with a significance level of 0.481 far greater than the specified significance level of 0.05, Government Complexity has no significant effect on the Required Level of Local Government Financial Statements with Levels the significance of 0.364 is greater than the specified level of significance of 0.05.